The Evaporation Mechanism in the Wick of Copper Heat Pipes - Wong, Shwin-Chung (SpringerBriefs in Applied Sciences and Technology, 2014)
This book discusses the evaporation mechanism in the wick of copper heat pipes. The investigations are based on recent visualization experiments for operating horizontal flat-plate heat pipes.